KgPeeps.Co / Alya Farhani Sham … [et al.] - Sham, Alya Farhani; Nizam, Muhammad Nur Iman; Jalili, Nur Irdina; Marizan, Nur Fatehah Zulfah; Ibrahim, Sarah Nurfatihah (2022)
Planning a business may have looked like a piece of cake, but the truth is, only those who bear it know the struggle. Planning requires a lot of patience, to prepare one's self before embarking on a hectic world of entrepreneurship. Our partnership, KgPeeps.Co has done thorough research and planned our journey systematically. It is to ensure that we will be fully prepared should there be any hindrance that might slow down our business. This business plan is a comprehensive explanation of the operation and marketing strategies, budgeting as well as expenses that will occur throughout the entire operation. We have narrowed the scope of our starter targeted area, of which Jelebu, Negeri Sembilan. An application known as KgPeeps.Co will help the villagers, indigenous people and even those who have lost their income to get back on their feet. They can sell and promote their local products that cannot easily be accessed to the urbanite through online platforms. Free classes will be provided to these people by educating them the basics of marketing and entrepreneurship and even the basics of technology. By doing so, these people can be financially independent and thrive in business as well. To conclude, the ultimate goal of KgPeeps.Co is not only focusing on numbers of profits, but to help others to upgrade their income level and be independent with solely having to rely on financial aids.